FAKTOR-FAKTOR PENENTU KEBIJAKAN DEVIDEN PADA PERUSAHAAN YANG TERINDEKS SAHAM SYARIAH INDONESIA - Frieska Kirana Dewi; Eriana Kartadjumena (Jurnal Akuntansi Bisnis dan Ekonomi, 2020)
This research aims to investigate the influence of managerial ownership, profitability and investment opportunity set on dividend payout ratio for the companies that listed in the Indonesia Islamic Stock Index. The proxies consist are the level of insider ownership, return on equity, the market value equity to book value equity, and dividend payout ratio. The data are gained from the 260 financial statement of 52 companies that listed in the Indonesia Islamic Stock Index from period 2012 to 2016. The results showed that simultaneously the insider ownership, return on equity, and investment opportunities set have significant influence on the dividend payout ratio. In partially, the result showed that only investment opportunity set has a significant negative influence on the dividend payout ratio.Peneliti